Comparing Student and Teacher Perceptions of the Importance of Social Skills in a Self-Contained Setting - Morgan, Joseph John; Dobbins, Nicole; Hsiao, Yun-Ju; Brown, Nancy; Higgins, Kyle (Journal of the American Academy of Special Education Professionals, 2015)
Implementation of social skills deemed appropriate for use in school is important for student success. Students with emotional and behavioral disorders often fail to use these social skills, requiring intervention to facilitate their use. Results related to social skills interventions have been mixed; one suggested reason for this is the lack of cultural relevance these social skills have to the lives of students. This study was designed to determine (a) the perceptions of students and teachers in a self-contained school setting of the importance of commonly taught social skills and (b) if there were any differences between age, ethnicity, gender, or role (teacher or student) related to perceptions of importance. Although some differences were found among the categories of skills, results of this study indicated that, overall, students and teachers in a self-contained school setting felt social skills were important. Implications for research and practice related to social skills interventions are discussed.